DAMPAK INVESTASI PEMERINTAH BERUPA PENAMBAHAN PENYERTAAN MODAL NEGARA TERHADAP KINERJA KEUANGAN BUMN - Adhitya, Wisnu Purna; Solikin, Akhmad (Feb Universitas Dirgantara Marsekal Suryadarma, 2025)
The purpose of this study is to empirically investigate the relationship between government capital support and the financial performance of State-Owned Enterprises (SOEs) in terms of profitability ratios using Return on Assets (ROA), Return on Equity (ROE) and Return on Sales (ROS). The study used five years data in 2014-2018 with a total sample of 76 firms. Using control variables of Net Profit Margin, Total Asset Turnover, Debt to Equity Ratio, firm age and percentage of government ownership, the study finds that the government support has a negative effect on SOEs financial performance if measured by ROE and has no significant effect if measured by ROA or ROS. This finding indicates that during 2014-2018, the government capital supports were used more for operational and non-operational expenses which could not positively contribute to the net profit of the firms.Keywords: Financial performance, Government capital support, State owned enterprise